A method for removing perfluorinated compounds in water

Through the combination of Fe3O4/ZnO/Ag3PO4 composite nanomaterials and persulfate, photocatalytic oxidation technology is used to solve the problem of poor removal effect of perfluorinated compounds in water, achieving deep removal and recycling of catalysts.

CN118598267BActive Publication Date: 2025-01-21SHANGHAI INVESTIGATION DESIGN & RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411080852.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-01-21
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove perfluoro compounds, especially medium and long chain PFASs in water bodies, and traditional methods have problems of high cost, high energy consumption and high pollution.

Method used

Fe3O4/ZnO/Ag3PO4 composite nanomaterials are combined with persulfate, and the persulfate catalytic oxidative degradation reaction is coupled through photocatalytic oxidation to achieve deep removal of perfluorinated compounds in water.

Benefits of technology

This method can significantly improve the removal rate and defluorination rate of perfluorinated compounds, reduce the cost and pollution of the catalyst, and the catalyst material is recyclable, making it suitable for medium-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118598267B_ABST
    Figure CN118598267B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of water pollution control, and in particular to a method for removing perfluorinated compounds in water. The present invention combines the photocatalysis and persulfate catalysis of Fe3O4 / ZnO / Ag3PO4 composite nanomaterials in a heterogeneous catalytic form to form a visible light-persulfate coupling (Vis-persulfate) system dominated by photocatalytic oxidation and having persulfate catalytic oxidation, which is used to remove perfluorinated compounds in water under simulated sunlight, and uses the magnetic core Fe3O4 to achieve convenient separation and recovery of Fe3O4 / ZnO / Ag3PO4 composite nanomaterials. The coupled water treatment technology provided by the present invention can make up for the defects of the current ultraviolet advanced oxidation technology, such as low visible light utilization, narrow pH application range, incomplete degradation of perfluorinated compounds, and difficult separation and recovery of catalysts, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water pollution control, in particular to a method for removing perfluorinated compounds in water. Background Art

[0002] Per- and Polyfluoroalkyl Substances (PFASs) are a class of synthetic compounds in which all or part of the hydrogen atoms on the carbon skeleton are replaced by fluorine atoms. They are widely used as surfactants in textiles, electroplating, fire protection and other fields. As a class of persistent organic pollutants, PFASs continue to accumulate in various environmental media. A large number of studies have shown that PFASs have potential biological toxicity, and their presence in the environment will pose a huge threat to human health and ecological safety.

[0003] The water environment is one of the most important destinations for PFASs. However, due to the high thermal and chemical stability of PFASs, conventional water treatment technologies have been shown to have little effect on the removal of PFASs. How to effectively control PFASs in water has become a problem that needs to be solved urgently. Physical technologies such as adsorption and membrane filtration can separate and enrich PFASs from water, but some high-cost, high-energy, and high-pollution methods such as high-temperature incineration are still required for further treatment. In contrast, some emerging chemical degradation technologies, such as electrochemical oxidation technology, photochemical technology, and low-temperature plasma technology, have attracted much attention in recent years because they can achieve direct degradation and removal of PFASs. Among the above-mentioned chemical degradation technologies, photochemical technologies based on ultraviolet light, especially UV-based advanced oxidation processes (UV-AOPs) and UV-based advanced reduction processes (UV-ARPs), not only have the advantages of being environmentally friendly, mild reaction conditions, and easy operation, but have also been proven to have good effects in degrading PFASs in recent years, providing an efficient technical solution for controlling PFASs in water. However, whether it is the UV-AOPs system or the UV-ARPs system, it takes a long reaction time to achieve a high degradation rate and defluorination rate of PFASs. When applied to engineering scale, attention must be paid to the safety and energy efficiency of the ultraviolet light source, as well as the dosage of oxidants, catalysts and reductants, so as to achieve low-cost and high-efficiency removal of PFASs. In addition, it is almost difficult to achieve complete defluorination with UV-AOPs or UV-ARPs alone, and the short-chain PFASs produced also have toxic effects. The possibility of combining with other physical, chemical or biological processes at the front or back end of UV-AOPs or UV-ARPs should be explored to achieve deep defluorination of PFASs. In addition, many current studies focus on long-chain perfluorinated compounds such as PFOA (perfluorooctane carboxylic acid), PFOS (perfluorooctane sulfonic acid), perfluoroalkyl carboxylic acids (PFCAs) and 6:2 fluorinated unsaturated carboxylic acid (6:2FTUCA), and have achieved good degradation and defluorination rates. However, for other medium- and long-chain PFASs such as perfluorohexanoic acid (PFHxA) and perfluoroheptanoic acid (PFHpA), there is currently little research and similar technologies have not been very effective in treating them.

[0004] Semiconductor photocatalysis is a green, efficient and promising method for treating water pollution. Its basic principle is that under the excitation of light, the electrons in the valence band of the semiconductor jump to the conduction band to generate electron-hole pairs, which in turn form superoxide radicals (·O 2- ) and hydroxyl radicals (·OH), these two free radicals and holes (h +) can decompose organic pollutants in water into small molecular organic matter such as H2O and CO2. In recent years, silver phosphate (Ag3PO4) has attracted more and more attention as a new type of visible light-driven catalytic material due to its significant advantages such as high quantum efficiency (about 90%), narrow band gap (about 2.4 eV), non-toxicity and low secondary pollution. However, with the continuous deepening of research, some defects have also been found. Due to the poor stability of Ag3PO4, photocorrosion is prone to occur during the photocatalytic process. In addition, its high cost seriously limits its large-scale application. In order to further improve its photocatalytic activity and stability, researchers have modified it in various ways, namely morphology regulation, element doping, precious metal deposition, and heterojunction construction. Among them, constructing a heterojunction generally refers to compounding with other semiconductors. Once this heterojunction is formed, it often obtains a higher separation efficiency of electron-hole pairs than other methods, and thus has a higher photocatalytic activity. Common heterojunctions are type II and type Z, such as ZnO@Ag3PO4, Ag3PO4 / TiO2-x, Ag3PO4 / g-C3N4, Ag3PO4 / WO3, Ag3PO4 / Bi2S3 / Bi2O3 and other heterojunctions. For the Z-type heterojunction, the photogenerated electrons will migrate from the more positive conduction band of the two semiconductors to the valence band of the other semiconductor, making the electrons on the conduction band have stronger reduction ability, and correspondingly making the holes of the semiconductor with a more positive valence band have stronger oxidation ability. As an outstanding semiconductor material, ZnO is widely used in the field of photocatalysis because of its low cost, high quantization rate, suitable bandgap width, and good photocatalytic activity. However, it has three major defects: first, its utilization rate of visible light is low; second, in the process of electron migration, due to the wide bandgap, some electron-hole pairs will recombine, reducing its photocatalytic activity; third, the particle size of ZnO is very small, and it is difficult to recover it through conventional centrifugation and separation, resulting in its high cost. In addition, due to its small particles, it is easy to agglomerate in aqueous solution, and its dispersion is very low, which affects the catalytic efficiency and greatly limits its industrial application. Therefore, how to obtain a multi-effect ZnO / Ag3PO4 catalyst with strong stability, easy separation, and high utilization rate of solar light through material design and synthesis, and use ultraviolet advanced oxidation technology to couple other processes to achieve deep removal of perfluorinated compounds in water bodies, while achieving convenient separation and recovery of materials and reducing their secondary hazards to the water environment, has become the focus and difficulty of research in this field. Summary of the invention

[0005] In view of the shortcomings of the existing perfluorinated compound removal technology in water, the purpose of the present invention is to provide a method for photocatalytic oxidation coupled with persulfate catalytic oxidation to degrade perfluorinated compounds in water, which can achieve deep removal of perfluorinated compounds in water and the catalyst material can be recovered.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a method for removing perfluorinated compounds in water, comprising the following steps: mixing water containing perfluorinated compounds with Fe3O4 / ZnO / Ag3PO4 composite nanomaterials and persulfate, and degrading the perfluorinated compounds in the reaction system by photocatalytic oxidation coupled with persulfate catalytic oxidation under sunlight or simulated sunlight conditions.

[0008] The second aspect of the present invention provides a method for preparing the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial, comprising the following steps:

[0009] (1) adding the activated Fe3O4 nanocrystal clusters into a zinc salt solution and dispersing them evenly to obtain a mixed solution;

[0010] (2) heating the mixed solution in an inert atmosphere, adding alkaline solution dropwise under magnetic stirring, controlling the end point pH of the system to be 11±0.5, and reacting to obtain Fe3O4 / ZnO;

[0011] (3) Add Fe3O4 / ZnO to AgNO3 solution, mix well, add hydrogen phosphate solution dropwise while stirring, react fully, and let stand to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] 1. The Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in the present invention is a new type of magnetic "dual-effect catalyst" with both visible light catalytic activity and persulfate catalytic activity. The method of the present invention mixes water containing perfluorinated compounds with the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial and persulfate, and constructs a coupled catalytic oxidation system composed of visible light response and persulfate catalysis with the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial as a catalyst, which gives full play to the "bridging" effect of the dual-effect catalyst, while enhancing the quantization efficiency, effectively prolonging the life of the active species, broadening the pH application range of the system, and playing a significant synergistic role in the oxidative degradation of highly toxic and high-concentration pollutants.

[0014] 2. The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial provided by the present invention has the characteristics of simple process, mild conditions, uniform heating, energy saving and high efficiency, easy control, etc. The preparation conditions and materials are universal, the product morphology is stable and the purity is high, and the product processing is convenient and concise, which is suitable for medium-scale industrial production.

[0015] 3. Compared with other oxidants such as H2O2 and O3, SO4 - · Lower cost; compared with ·OH, SO4- Longer life (the half-life of OH is 10 -9 s, SO4 - The half-life is 4×10 -6 s), can maintain a high redox potential in a wide pH range, can induce the production of ·OH, and react with SO4 - The dual free radical system is formed together, which has stronger oxidation ability, low cost and flexible technology. The present invention couples it with ultraviolet oxidation technology to make up for the defects of the current ultraviolet advanced oxidation technology, such as low utilization rate of visible light, narrow pH application range, incomplete degradation of perfluorinated compounds, and difficulty in separating and recovering catalysts.

[0016] 4. The technical method provided by the present invention is not only applicable to the removal of perfluorinated compounds in water bodies, but also applicable to the removal of perfluorinated compounds in the atmosphere or soil, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 These are SEM images of Fe3O4 nanocrystal clusters, Fe3O4 / ZnO and Fe3O4 / ZnO in Example 1, wherein a is the Fe3O4 nanocrystal cluster in Example 1, b is the Fe3O4 / ZnO in Comparative Example 1, and c is the Fe3O4 / ZnO in Example 1.

[0018] Figure 2 This is the SEM image of the product Fe3O4 / ZnO / Ag3PO4 obtained in Example 1 of the present invention.

[0019] Figure 3 These are the XRD diagrams of the products Fe3O4, Fe3O4 / ZnO, and Fe3O4 / ZnO / Ag3PO4 obtained in Example 1 of the present invention.

[0020] Figure 4 The UV-visible absorption spectra of ZnO carbon nanotubes, the products Fe3O4 / ZnO obtained in Example 1, and Fe3O4 / ZnO / Ag3PO4.

[0021] Figure 5 These are the magnetization curves of the products Fe3O4, Fe3O4 / ZnO, and Fe3O4 / ZnO / Ag3PO4 obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention designs and synthesizes a novel magnetic "dual-effect catalyst" Fe3O4 / ZnO / Ag3PO4 composite nanomaterial with simple and controllable preparation, recyclable magnetism, high catalytic performance, stable structure, and both visible light catalytic activity and persulfate catalytic activity. Under simulated sunlight irradiation, the accumulated electrons in the CB of ZnO and the holes in the VB of Ag3PO4 can participate in reduction and oxidation reactions respectively. Finally, the electrons in the CB of ZnO have more negative potential, which can reduce molecular oxygen to form O2 - The holes on the valence band of Ag3PO4 have more positive potentials and can oxidize H2O to generate OH, making the redox ability of the composite nanomaterial stronger, and can use visible light to achieve defluorination and deep catalytic degradation of perfluorinated compounds; at the same time, ZnO can use the generated electron-hole pairs to successfully activate persulfate to generate SO4 - · and ·OH, while the Ag in Ag3PO4 + As the transition metal with the best catalytic effect on persulfate, it can also catalyze the decomposition of persulfate to produce SO4 - ·, Fe3O4 can be used as a co-catalyst of persulfate and can also be magnetized to achieve material recycling; the whole system constitutes a visible light-persulfate coupling (Vis-persulfate) system dominated by photocatalytic oxidation and catalytic oxidation of persulfate, which can be used to remove perfluorinated compounds in water, and can achieve defluorination and deep degradation of perfluorinated compounds.

[0023] The method for removing perfluorinated compounds in water of the present invention is described in detail below.

[0024] The first aspect of the present invention provides a method for removing perfluorinated compounds in water, comprising the following steps: mixing water containing perfluorinated compounds with Fe3O4 / ZnO / Ag3PO4 composite nanomaterials and persulfate, and degrading the perfluorinated compounds in the reaction system by photocatalytic oxidation coupled with persulfate catalytic oxidation under sunlight or simulated sunlight conditions.

[0025] In some embodiments of the present invention, the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial is composed of Fe3O4 nanocrystal clusters, ZnO nanotubes and Ag3PO4 nanoparticles, the Fe3O4 nanocrystal clusters are encapsulated inside the ZnO nanotubes, and the Ag3PO4 nanoparticles are loaded on the ZnO nanotubes.

[0026] In some embodiments of the present invention, the persulfate is selected from peroxymonosulfate or peroxydisulfate. The peroxymonosulfate is selected from any one or more of potassium peroxymonosulfate (KHSO5·0.5KHSO4·0.5K2SO4) or sodium peroxymonosulfate (NaHSO5·0.5NaHSO4·0.5Na2SO4). The peroxydisulfate is selected from any one or more of sodium peroxydisulfate (Na2S2O8), potassium peroxydisulfate (K2S2O8) or ammonium peroxydisulfate ((NH4)2S2O8).

[0027] In some embodiments of the present invention, the light source for simulating sunlight is selected from any one or more of a xenon lamp, a halogen lamp or an LED lamp.

[0028] In some embodiments of the present invention, the mass of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in the reaction system is 0.01~0.05 g / L, which can be 0.01~0.02 g / L, 0.02~0.03 g / L, 0.03~0.04 g / L, or 0.04~0.05 g / L; in some embodiments of the present invention, the concentration of persulfate in the reaction system is 0.1~1mmol / L, which can be 0.1~0.2 mmol / L, 0.2~0.3 mmol / L, 0.3~0.4 mmol / L, 0.4~0.5 mmol / L, 0.5~0.6 mmol / L, 0.6~0.7 mmol / L, 0.7~0.8 mmol / L, 0.8~0.9 mmol / L, or 0.9~1 mmol / L, preferably 0.25~0.3 mmol / L.

[0029] In some embodiments of the present invention, the pH of the reaction system is 6.0-9.0, and may be 6.0-6.5, 6.5-7.0, 7.0-7.5, 7.5-8.0, 8.0-8.5, or 8.5-9.0; preferably, it is 6.5-7.5.

[0030] In some embodiments of the present invention, the degradation time is 0.5 to 24 h, and can be 0.5 to 1 h, 1 to 2 h, 2 to 4 h, 4 to 8 h, 8 to 12 h, 12 to 16 h, 16 to 20 h, or 20 to 24 h, and is preferably 3 to 12 h.

[0031] In some embodiments of the present invention, the perfluorinated compound is a long-chain perfluorinated compound or a medium-chain perfluorinated compound; further, the long-chain perfluorinated compound includes perfluorooctane carboxylic acid (PFOA) and perfluorooctane sulfonic acid (PFOS); the medium-chain perfluorinated compound includes perfluorohexanoic acid and perfluoroheptanoic acid.

[0032] In some embodiments of the present invention, after the reaction is completed, the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial is separated and recovered from the system by utilizing its magnetic properties.

[0033] In some embodiments of the present invention, the method for preparing the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial comprises the following steps:

[0034] (1) adding the activated Fe3O4 nanocrystal clusters into a zinc salt solution and dispersing them evenly to obtain a mixed solution;

[0035] (2) heating the mixed solution in an inert atmosphere, adding alkaline solution dropwise under magnetic stirring, controlling the end point pH of the system to be 11±0.5, and reacting to obtain Fe3O4 / ZnO;

[0036] (3) Add Fe3O4 / ZnO to AgNO3 solution, mix well, add hydrogen phosphate solution dropwise while stirring, react fully, and let stand to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials.

[0037] In some embodiments of the present invention, in step (1), the Fe3O4 nanocrystal clusters are prepared by a solvothermal method.

[0038] In some embodiments of the present invention, in step (1), the activation treatment operation is to place the Fe3O4 nanocrystal clusters in an activator solution for ultrasonic treatment; preferably, the activator is sodium citrate or sodium malate; in the present invention, the solvent of the solution is deionized water unless otherwise specified; in some embodiments of the present invention, the mass fraction of the activator in the activator solution is 1%~3%, which can be 1%~2%, or 2%~3%; in some embodiments of the present invention, the ultrasonic treatment time is 20~40 min, which can be 20~25 min, 25~30 min, 30~35 min, or 35~40 min; in some embodiments of the present invention, after the ultrasonic treatment, it is necessary to stand for 0.5~5 h, which can be 0.5~1 h, 1~2 h, 2~3 h, 3~4 h, or 4~5 h. Example 1 The SEM characterization results of Fe3O4 / ZnO prepared by Fe3O4 nanocrystal clusters after citric acid activation treatment are shown in Figure 1. Figure 1 As shown in Figure c, it can be seen that the Fe3O4 nanocrystal clusters are successfully encapsulated inside the ZnO nanotubes, while the SEM characterization results of Fe3O4 / ZnO prepared by using Fe3O4 nanocrystal clusters without activation treatment in Comparative Example 1 are as follows Figure 1As shown in Figure b, it can be seen that the ZnO nanotubes and the Fe3O4 nanocrystal clusters are randomly distributed, and the Fe3O4 nanocrystal clusters are not encapsulated inside the ZnO nanotubes. Therefore, activation treatment is one of the key factors for the successful preparation of Fe3O4 / ZnO materials. This is because citrate or malate can complex Zn 2+ , which enables it to find attachment sites on the Fe3O4 surface and lay the foundation for the nucleation and growth of wurtzite; on the other hand, the -COOH structures rich in citrate or malate can complex with the hydroxyl groups on the surface of Fe3O4 and ZnO respectively, serving as a bridge connecting the two, improving the binding force between the two and helping the formation of Fe3O4 / ZnO composite nanomaterials.

[0039] In some embodiments of the present invention, in step (1), the zinc salt of the zinc salt solution is selected from any one or more of zinc acetate, zinc sulfate, zinc chloride or zinc nitrate, preferably zinc acetate; the molar concentration of the zinc salt solution is 0.001-0.01 mol / L, which can be 0.001-0.002 mol / L, 0.002-0.004 mol / L, 0.004-0.006 mol / L, 0.006-0.008 mol / L, or 0.008-0.01 mol / L, preferably 0.002-0.006 mol / L.

[0040] In some embodiments of the present invention, in step (1), the dispersion method is ultrasonic treatment, and the time of ultrasonic treatment is 15 to 60 min, which can be 15 to 20 min, 20 to 25 min, 25 to 30 min, 30 to 35 min, 35 to 40 min, 40 to 45 min, 45 to 50 min, 50 to 55 min, or 55 to 60 min.

[0041] In some embodiments of the present invention, in step (2), the inert atmosphere is selected from one or more of nitrogen or argon.

[0042] In some embodiments of the present invention, in step (2), the heating temperature is 25-100°C, and can be 25-30°C, 30-40°C, 40-50°C, 50-60°C, 60-70°C, 70-80°C, 80-90°C, or 90-100°C, preferably 50-90°C.

[0043] In some embodiments of the present invention, in step (2), the speed of the magnetic stirring is 120-180 r·min -1 , can be 120~130 r·min -1 , 130~140 r·min -1, 140~150 r·min -1 , 150~160 r·min -1 , 160~170 r·min -1 , 170~180 r·min -1 , preferably 140~150 r·min -1 .

[0044] In some embodiments of the present invention, in step (2), the alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution or ammonia solution; the concentration of the sodium hydroxide solution is 0.03-0.05 mol / L; the concentration of the potassium hydroxide solution is 0.04-0.05 mol / L; the concentration of the ammonia solution is 5 mol / L.

[0045] In some embodiments of the present invention, in step (2), the reaction time is 2 to 12 h, can be 2 to 4 h, 4 to 6 h, 6 to 8 h, 8 to 10 h, or 10 to 12 h, preferably 5 to 12 h.

[0046] In some embodiments of the present invention, in step (2), after the reaction is completed, the product is further washed and dried; the washing is performed by alternating rinsing with ethanol and deionized water, the washing times are three times; the drying is performed by vacuum drying, the drying temperature is 50-70°C.

[0047] In some embodiments of the present invention, in step (3), the hydrogen phosphate is selected from Na2HPO4 or K2HPO4.

[0048] In some embodiments of the present invention, in step (3), the amount of AgNO3 and hydrogen phosphate is such that m(Ag3PO4):m(Fe3O4 / ZnO)=10%~40%, which can be 10%~15%, 15%~20%, 20%~25%, 25%~30%, 30%~35%, or 35%~40%; specifically, the amount of AgNO3 solution and hydrogen phosphate solution is such that the mass ratio of Ag3PO4 generated in the reaction system to the mass ratio of Fe3O4 / ZnO in the reaction system is 10%~40%; preferably 20%~40%.

[0049] In some embodiments of the present invention, in step (3), the reaction time is 0.5 to 6 h, and can be 0.5 to 1 h, 1 to 2 h, 2 to 3 h, 3 to 4 h, 4 to 5 h, or 5 to 6 h.

[0050] In some embodiments of the present invention, in step (3), the reaction further comprises standing after completion, and the standing time is 0.5 to 12 h, which can be 0.5 to 1 h, 1 to 2 h, 2 to 4 h, 4 to 6 h, 6 to 8 h, or 8 to 12 h, preferably 6 to 8 h.

[0051] In some embodiments of the present invention, in step (3), after the reaction is completed, the product is further dried once, washed and dried twice; in some embodiments of the present invention, the primary drying, washing and secondary drying are performed after standing; in some embodiments of the present invention, the washing is rinsing with deionized water, and the number of washing times is three times; the drying temperature of the primary drying is 50-80°C, which can be 50-60°C, 60-70°C, or 70-80°C, preferably 60-70°C, and more preferably 70°C; the drying temperature of the secondary drying is 35-50°C, which can be 35-40°C, 40-45°C, or 45-50°C, and preferably 45°C.

[0052] The principle of the invention is as follows: Fe3O4 nanocrystal clusters are used as precursors, and their surfaces are rich in carboxyl and hydroxyl groups through citrate activation, and then they are immersed in a solution rich in zinc ions, and zinc ions are complexed on the surface of Fe3O4 by carboxyl and hydroxyl groups to generate crystal seeds on the surface of Fe3O4, and then ZnO crystal nuclei are formed under the action of an alkaline solution, and then ZnO hollow nanotubes are generated on the surface of the Fe3O4 nanocrystal clusters through Oswald ripening and epitaxial growth, and then Ag3PO4 nanoparticles are loaded on the ZnO nanotubes by a coprecipitation method, so as to obtain a new type of magnetic "double-effect catalyst" Fe3O4 / ZnO / Ag3PO4 composite nanomaterial with both visible light catalytic activity and persulfate catalytic activity, which is magnetically recyclable, has high catalytic performance, and is structurally stable.

[0053] The valence band (VB) and conduction band (CB) of ZnO are 2.7 and -0.5 eV, respectively, and the VB and CB of Ag3PO4 are 2.9 and 0.45 eV, respectively. When the pH of water is 7.0, the standard redox potential of H2O / ·OH is about 2.7~2.8 eV relative to the general hydrogen electrode (NHE), and the standard redox potential of O2 / ·O2 - The standard redox potential of ZnO is -0.3eV, so h+ VB The Ag3PO4 CB cannot oxidize H2O to generate ·OH. - Cannot reduce O2 to O2 -. Since the valence band potential and conduction band potential of ZnO are more negative than those of Ag3PO4, after compounding with Ag3PO4, the electrons of Ag3PO4CB can migrate to the VB of ZnO, thus forming a Z-type heterojunction and improving the separation efficiency of electrons and holes. Under simulated sunlight, the accumulated electrons in the CB of ZnO and the holes in the VB of Ag3PO4 can participate in reduction and oxidation reactions, respectively. Ultimately, the electrons in the CB of ZnO have more negative potential and can reduce molecular oxygen to form ·O2 - The holes on the valence band of Ag3PO4 have more positive potentials, which can oxidize H2O to generate OH, making the redox ability of the composite nanomaterial stronger, and can also use visible light to achieve defluorination and deep catalytic degradation of perfluorinated compounds.

[0054] At the same time, ZnO can successfully activate persulfate to generate SO4 using the generated electron-hole pairs. - · and ·OH, while the Ag in Ag3PO4 + As the transition metal with the best catalytic effect on persulfate, it can also catalyze the decomposition of persulfate to produce SO4 - ·, Fe3O4 can be used as a co-catalyst of persulfate and can also impart magnetism to achieve material recycling. Finally, a visible light-persulfate coupling (Vis-persulfate) system dominated by photocatalytic oxidation and catalytic oxidation of persulfate is formed, which is used to promote the removal of perfluorinated compounds in water bodies and achieve further defluorination and deep catalytic degradation of perfluorinated compounds.

[0055] Taking the degradation of PFOA and PFOS as an example, under the action of Fe3O4 / ZnO / Ag3PO4 composite nanomaterials, ·OH and ·O2 - and hydrated electrons - , and the strong oxidizing SO4 generated by persulfate activation - ·, attacking the head group of perfluorinated compounds. For PFOS, during the degradation process, PFOS can be converted into anionic PFOA through a series of reactions, which reacts with SO4· - The reaction generates C7F 15 COO·intermediate, the perfluoroalkyl formed by decarboxylation of the intermediate is hydrolyzed under the action of ·OH to form an unstable perfluoroalcohol (C7F 15 OH), followed by elimination and hydrolysis to generate C6F 13 COO·"decarboxylation-hydroxylation-HF elimination-hydrolysis (DHEH)" cycle, that is, each cycle removes one -CF2 unit until complete defluorination and forms the final product F- and CO2.

[0056] The specific embodiments of the present invention are further described in detail below in conjunction with preferred embodiments. When the embodiments provide numerical ranges, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, as those skilled in the art grasp the prior art and record the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0057] Example 1

[0058] A method for removing perfluorinated compounds in water comprises the following steps:

[0059] Step 1: Prepare Fe3O4 nanocrystal clusters by solvothermal method, then take 0.05g Fe3O4 nanocrystal clusters and place them in 2% sodium citrate solution for ultrasonic treatment for 30 min, let it stand for 2 h, and obtain Fe3O4 nanocrystal clusters after activation treatment. The SEM characterization results of Fe3O4 nanocrystal clusters are shown in Figure 1 As shown in a.

[0060] Step 2: Place the activated Fe3O4 nanocrystal clusters in a 0.005 mol / L zinc acetate solution and ultrasonically disperse them for 30 minutes to obtain a mixed solution.

[0061] Step 3: Transfer the mixed solution to a three-necked flask and heat the system to 90 °C and 145 r / min under argon protection. -1 Under magnetic stirring, 0.03 mol / L sodium hydroxide solution was slowly added dropwise to control the end point pH of the system to 11±0.5. The reaction was continued for 6 h. The product was washed alternately with ethanol and deionized water and dried under vacuum at 60 °C to obtain Fe3O4 / ZnO. The SEM characterization results of the product Fe3O4 / ZnO are shown in Figure 1 As shown in c.

[0062] Step 4: Prepare 0.5 mol / L AgNO3 solution and 0.167 mol / L Na2HPO4 solution, add Fe3O4 / ZnO prepared in the third step to the AgNO3 solution, slowly add Na2HPO4 solution dropwise under stirring, control the mass ratio of Ag3PO4 to Fe3O4 / ZnO to be 20%, fully react for 4 h, let stand for 6 h, dry at 70 °C, rinse three times with deionized water, and dry at 45 °C to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials. The SEM characterization results of Fe3O4 / ZnO / Ag3PO4 composite nanomaterials are shown in Figure 2. Figure 2 shown.

[0063] Figure 1 Figure a is the SEM image of the Fe3O4 nanocrystal cluster in Example 1. Figure 1 Figure c is the SEM image of Fe3O4 / ZnO in Example 1. Figure 1 A and Figure 1 In Figure c, it can be seen that the Fe3O4 nanocrystal clusters in the Fe3O4 / ZnO prepared in the third step of Example 1 are encapsulated in the ZnO hollow nanotubes to form a composite material.

[0064] Figure 2 The SEM image of the product Fe3O4 / ZnO / Ag3PO4 obtained in Example 1 of the present invention. Figure 2 It can be seen that the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial obtained in the fourth step is a composite material of Fe3O4 / ZnO and Ag3PO4, and the Ag3PO4 nanoparticles are successfully loaded on the ZnO nanotubes of Fe3O4 / ZnO, forming a Z-type heterojunction with ZnO.

[0065] Figure 3 The XRD diagrams of the products Fe3O4, Fe3O4 / ZnO, and Fe3O4 / ZnO / Ag3PO4 obtained in Example 1 of the present invention are shown in FIG. Figure 3It can be seen that the peaks of the composite nanomaterial at 2θ=30.1°, 35.4°, 43.2°, 53.4°, 56.9° and 62.5° are the characteristic peaks of Fe3O4 (JCPDS card number 65-3107), corresponding to the (220), (311), (400), (511) and (440) crystal planes of Fe3O4 with face-centered cubic structure; at 2θ=31.769°, 34.421°, 36.252°, 47.538°, 56.6 The characteristic peaks of zincite ZnO (JCPDS card number 36-1451) appear at 02°, 62, 862°, 66, 378°, 67.961°, and 69.098°, corresponding to the (100), (002), (101), (102), (110), (103), (200), (112), and (201) crystal planes, respectively. The appearance of zincite zinc oxide is usually caused by doping, which also indicates that there may be an interaction between Fe3O4 and ZnO. 3+ Replaces the original Zn in the crystal 2+ The position of the ZnO photogenerated hole-electron pair leads to defect sites in the lattice, which is conducive to the separation of ZnO photogenerated hole-electron pairs, produces a higher concentration of active oxidative groups, and prolongs the existence time of •OH; the peaks of the composite nanomaterial at 2θ=20.9°, 29.7°, 33.3°, 36.6°, 42.5°, 47.8°, 52.7°, 55.02°, 57.3° and 61.7° are the characteristic peaks of Ag3PO4 (JCPDS card number 06-0505), corresponding to its (110), (200), (210), (211), (220), (310), (222), (320), (321) and (400) crystal planes, respectively. The above phenomenon indicates the successful composite of Fe3O4 / ZnO / Ag3PO4 composite nanomaterials, and also proves that Figure 2 The conclusions drawn.

[0066] Figure 4 The UV-visible absorption spectra of ZnO carbon nanotubes, Fe3O4 / ZnO and Fe3O4 / ZnO / Ag3PO4 obtained in Example 1 are shown in Table 1. Figure 4 It can be seen that due to the introduction of Ag3PO4, the light response range of Fe3O4 / ZnO / Ag3PO4 is wider, which can be expanded from the ultraviolet light region to the visible light region. Since ultraviolet light accounts for only 7% of sunlight, and visible light accounts for 43% of sunlight, the widening of the material's light response range can greatly improve the utilization rate of sunlight in practical applications.

[0067] Figure 5 The magnetization curves of Fe3O4, Fe3O4 / ZnO, and Fe3O4 / ZnO / Ag3PO4 obtained in Example 1 of the present invention are shown in FIG. Figure 5 It can be seen that although the magnetism of the product Fe3O4 / ZnO / Ag3PO4 composite nanomaterial is greatly reduced compared with the single Fe3O4 nanocrystal cluster, it still meets the requirements of magnetic separation (Ms greater than 1emu / g) and still has superparamagnetism. In practical applications, it can be easily separated and recovered under the action of a magnetic field.

[0068] Example 2

[0069] A method for removing perfluorinated compounds in water comprises the following steps:

[0070] Step 1: Prepare ferroferric oxide (Fe3O4) nanocrystal clusters by solvothermal method, then take 0.075g of Fe3O4 nanocrystal clusters and place them in 3% sodium malate solution for ultrasonic treatment for 30 min, let it stand for 2 h, and obtain activated Fe3O4 nanocrystal clusters.

[0071] Step 2: Place the activated Fe3O4 nanocrystal clusters in a 0.003 mol / L zinc chloride solution and ultrasonically disperse them for 40 minutes to obtain a mixed solution.

[0072] Step 3: Transfer the mixed solution to a three-necked flask and heat the system to 80 °C and 175 r / min under nitrogen protection. -1 Under magnetic stirring, 0.04 mol / L potassium hydroxide solution was slowly added dropwise to control the end point pH of the system to be 11±0.5. The reaction was carried out for 5 h. The product was washed alternately with ethanol and deionized water and dried in vacuum at 60 °C to obtain Fe3O4 / ZnO.

[0073] Step 4: prepare 0.3 mol / L AgNO3 solution and 0.1 mol / L K2HPO4 solution, add the Fe3O4 / ZnO prepared in the third step into the AgNO3 solution, slowly add Na2HPO4 solution dropwise under stirring, control the mass ratio of Ag3PO4 to Fe3O4 / ZnO to be 30%, react fully for 4 h, let stand for 6 h, dry at 60 °C, rinse three times with deionized water and dry at 40 °C to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials.

[0074] Example 3

[0075] A method for removing perfluorinated compounds in water comprises the following steps:

[0076] Step 1: Prepare ferroferric oxide (Fe3O4) nanocrystal clusters by solvothermal method, then take 0.075g of Fe3O4 nanocrystal clusters and place them in 1% sodium citrate solution for ultrasonic treatment for 40 min, let it stand for 3 h, and obtain Fe3O4 nanocrystal clusters after activation treatment.

[0077] Step 2: Place the activated Fe3O4 nanocrystal clusters in a 0.004 mol / L zinc nitrate solution and ultrasonically disperse them for 40 minutes to obtain a mixed solution.

[0078] Step 3: Transfer the mixed solution to a three-necked flask and heat the system to 80 °C and 120 r / min under nitrogen protection. -1 Under magnetic stirring, 0.05 mol / L sodium hydroxide solution was slowly added dropwise to control the end point pH of the system to be 11±0.5. The reaction was carried out for 6 h. The product was washed alternately with ethanol and deionized water and dried in vacuum at 60 °C to obtain Fe3O4 / ZnO.

[0079] Step 4: prepare 0.6 mol / L AgNO3 solution and 0.2 mol / L Na2HPO4 solution, add the Fe3O4 / ZnO prepared in the third step to the AgNO3 solution, slowly add Na2HPO4 solution dropwise under stirring, control the mass ratio of Ag3PO4 to Fe3O4 / ZnO to be 25%, react fully for 4 h, let stand for 6 h, dry at 75 °C, rinse three times with deionized water and dry at 50 °C to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials.

[0080] Example 4

[0081] A method for removing perfluorinated compounds in water comprises the following steps:

[0082] Step 1: Prepare ferroferric oxide (Fe3O4) nanocrystal clusters by solvothermal method, then take 0.1 g of Fe3O4 nanocrystal clusters and place them in 3% sodium citrate solution for ultrasonic treatment for 20 min, let it stand for 5 h, and obtain activated Fe3O4 nanocrystal clusters.

[0083] Step 2: Place the activated Fe3O4 nanocrystal clusters in a 0.01 mol / L zinc sulfate solution and ultrasonically disperse them for 60 minutes to obtain a mixed solution.

[0084] Step 3: Transfer the mixed solution to a three-necked flask and heat the system to 100 °C and 125 r / min under nitrogen protection. -1 Under magnetic stirring, 0.05 mol / L potassium hydroxide solution was slowly added dropwise to control the end point pH of the system to be 11±0.5. The reaction was carried out for 10 h. The product was washed alternately with ethanol and deionized water and dried in vacuum at 50 °C to obtain Fe3O4 / ZnO.

[0085] Step 4: prepare 0.6 mol / L AgNO3 solution and 0.2 mol / L K2HPO4 solution, add the Fe3O4 / ZnO prepared in the third step to the AgNO3 solution, slowly add Na2HPO4 solution dropwise under stirring, control the mass ratio of Ag3PO4 to Fe3O4 / ZnO to be 10%, react for 0.5 h, let stand for 12 h, dry at 50 °C, rinse three times with deionized water and dry at 35 °C to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials.

[0086] Example 5

[0087] A method for removing perfluorinated compounds in water comprises the following steps:

[0088] Step 1: Prepare ferroferric oxide (Fe3O4) nanocrystal clusters by solvothermal method, then take 0.06 g of Fe3O4 nanocrystal clusters and place them in 2% sodium citrate solution for ultrasonic treatment for 60 min, let it stand for 0.5 h, and obtain activated Fe3O4 nanocrystal clusters.

[0089] Step 2: Place the activated Fe3O4 nanocrystal clusters in a 0.001 mol / L zinc nitrate solution and ultrasonically disperse them for 15 minutes to obtain a mixed solution.

[0090] Step 3: Transfer the mixed solution to a three-necked flask and heat the system to 25 °C and 180 r·min under nitrogen protection. -1 Under magnetic stirring, 5 mol / L ammonia water was slowly added dropwise to control the end point pH of the system to be 11±0.5. The reaction was carried out for 12 h. The product was washed alternately with ethanol and deionized water and dried in vacuum at 70 °C to obtain Fe3O4 / ZnO.

[0091] Step 4: prepare 0.3 mol / L AgNO3 solution and 0.1 mol / L Na2HPO4 solution, add the Fe3O4 / ZnO prepared in the third step to the AgNO3 solution, slowly add Na2HPO4 solution dropwise under stirring, control the mass ratio of Ag3PO4 to Fe3O4 / ZnO to be 40%, react for 6 h, let stand for 0.5 h, dry at 80 °C, rinse three times with deionized water and dry at 40 °C to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials.

[0092] Example 6

[0093] The Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 1 or Example 4 is used in combination with sodium persulfate under simulated sunlight to remove perfluorooctane sulfonic acid in water. The specific operation is as follows:

[0094] 50 mL of 50 mg / L perfluorooctane sulfonic acid solution was prepared with deionized water and placed in a 100 mL beaker. The solution was irradiated with a xenon lamp and the pH was adjusted to 7±0.5 with diluted H2SO4 and NaOH. The Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 1 was added in an amount of 0.03 g / L (or the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 4 was added in an amount of 0.05 g / L). Then, sodium peroxydisulfate was added and mixed and stirred evenly. The concentration of sodium peroxydisulfate in the reaction system was 0.25 mmol / L. The solution was placed in a fume hood and mechanically stirred for 6 h. The reaction time was recorded as Group G1 (or Group G1-1).

[0095] Example 7

[0096] Different from the higher interfacial adsorption caused by the higher reactivity and lower surface tension of long-chain perfluorinated compounds, which makes it easier for long-chain perfluorinated compounds to directly react with active substances at the solid-liquid interface, medium-chain perfluorinated compounds have lower reactivity due to their own rigid structure limitations, and are relatively difficult to degrade and remove in water. In this example, the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 2 or Example 5 is used in combination with sodium persulfate under simulated sunlight to remove perfluoroheptanoic acid in water. The specific operation is as follows:

[0097] 50 mL of 50 mg / L perfluoroheptanoic acid solution was prepared with deionized water and placed in a 100 mL beaker. The solution was irradiated with a xenon lamp and the pH was adjusted to 7±0.5 with diluted H2SO4 and NaOH. The Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 2 was added in an amount of 0.04 g / L (or the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 5 was added in an amount of 0.01 g / L). Then, sodium peroxydisulfate was added and mixed and stirred evenly. The concentration of sodium peroxydisulfate in the reaction system was 0.3 mmol / L. The solution was placed in a fume hood and mechanically stirred for 6 h. The reaction was recorded as Group H1 (or Group H1-1).

[0098] Comparative Example 1

[0099] The same method as in Example 1 was used except that the Fe3O4 nanocrystal clusters were not activated, that is, the Fe3O4 nanocrystal clusters prepared by the first step of the solvothermal method were directly placed in a 0.005 mol / L zinc acetate solution for ultrasonic dispersion. The SEM characterization results of the obtained product Fe3O4 / ZnO are shown in FIG. Figure 1 As shown in b.

[0100] Comparative Example 2

[0101] Except that sodium persulfate was not added (i.e., only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 1 was added in an amount of 0.03 g / L), the rest was the same as Example 6 (denoted as Group G2).

[0102] Comparative Example 3

[0103] Except that the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial is not added (i.e., only sodium persulfate is added), the rest is the same as Example 6 (denoted as Group G3).

[0104] Comparative Example 4

[0105] Except that visible light was used instead of simulated sunlight (a 400 nm filter was added to filter out the ultraviolet light emitted by the xenon lamp light source) and Fe3O4 / ZnO / Ag3PO4 composite nanomaterials were not added (i.e., only sodium persulfate was added), the rest was the same as Example 6 (denoted as Group G4).

[0106] Comparative Example 5

[0107] The same procedures as in Example 6 (denoted as Group G5) were used except that visible light was used instead of simulated sunlight (a 400 nm filter was added to filter out the ultraviolet light emitted by the xenon lamp light source) and sodium persulfate was not added (only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 1 was added in an amount of 0.03 g / L).

[0108] Comparative Example 6

[0109] Except that sodium persulfate was not added (i.e., only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 2 was added in an amount of 0.04 g / L), the rest was the same as Example 5 (denoted as Group H2).

[0110] Comparative Example 7

[0111] Except that the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial is not added (i.e., only sodium persulfate is added), the rest is the same as Example 7 (denoted as Group H3).

[0112] Comparative Example 8

[0113] Except that visible light was used instead of simulated sunlight (a 400 nm filter was added to filter out the ultraviolet light emitted by the xenon lamp light source) and Fe3O4 / ZnO / Ag3PO4 composite nanomaterials were not added (i.e., only sodium persulfate was added), the rest was the same as Example 7 (denoted as Group H4).

[0114] Comparative Example 9

[0115] Except that visible light was used instead of simulated sunlight (a 400 nm filter was added to filter out the ultraviolet light emitted by the xenon lamp light source), and sodium persulfate was not added (i.e., only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 2 was added in an amount of 0.04 g / L), the rest was the same as Example 7 (denoted as Group H5).

[0116] The SEM characterization results of ZnO nanotubes in Fe3O4 / ZnO prepared in Comparative Example 1 are as follows: Figure 1 As shown in b, the SEM characterization results of Fe3O4 / ZnO prepared by Fe3O4 nanocrystal clusters after citric acid activation treatment in Example 1 (as shown in Figure 1 Comparison between (a) and (b) shows that the ZnO nanotubes and Fe3O4 nanoclusters are randomly distributed in the Fe3O4 / ZnO without citric acid activation treatment, and the Fe3O4 nanoclusters are not encapsulated inside the ZnO nanotubes. However, the Fe3O4 nanoclusters are successfully encapsulated inside the ZnO nanotubes in the Fe3O4 / ZnO with citric acid activation treatment, indicating that the activation treatment of Fe3O4 nanoclusters has an important influence on the successful composite of Fe3O4 nanoclusters and ZnO nanotubes.

[0117] The removal rate and defluorination rate of perfluorooctane sulfonic acid in the water of Example 6 and Comparative Examples 2 to 5 are shown in Table 1.

[0118] Table 1 Removal of PFOS in water of each treatment group

[0119]

[0120] As shown in Table 1, under the conditions of simulated sunlight, the Fe3O4 / ZnO / Ag3PO4 composite material and sodium peroxydisulfate were added to the G1 group (the Fe3O4 / ZnO / Ag3PO4 composite material prepared in Example 1) and the G1-1 group (the Fe3O4 / ZnO / Ag3PO4 composite material prepared in Example 4) at the same time, and the removal rate and defluorination rate of perfluorooctane sulfonic acid were higher, which were significantly higher than those of the G2 group (only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 1 was added) and the G3 group (only sodium peroxydisulfate was added). This is because the photocatalysis and persulfate catalysis of Fe3O4 / ZnO / Ag3PO4 are combined in a heterogeneous catalytic form to form a visible light-persulfate coupling (Vis-persulfate) system dominated by photocatalytic oxidation and with persulfate catalytic oxidation. The degradation mechanism is as follows: Under the action of the Fe3O4 / ZnO / Ag3PO4 composite material, the ·OH and ·O2 - and hydrated electrons - , and the strong oxidizing SO4 generated by persulfate activation -·, attacking the head group of PFOS. During the degradation process, PFOS can be converted into anionic PFOA through a series of reactions, which reacts with SO4 - ·Reaction generates C7F 15 COO·intermediate, the perfluoroalkyl formed by decarboxylation of the intermediate is hydrolyzed under the action of ·OH to form an unstable perfluoroalcohol (C7F 15 OH), followed by elimination and hydrolysis to generate C6F 13 COO·Then the cycle of “decarboxylation-hydroxylation-HF elimination-hydrolysis (DHEH)” is repeated, i.e. one −CF2 unit is removed in each cycle until the defluorination is complete and the final product F is formed. - The degradation rate and defluorination rate of PFOS in group G4 (only sodium persulfate was added) under visible light were lower than those in group G3 (only sodium persulfate was added) under simulated sunlight, indicating that the persulfate system can also be activated to produce SO4 under the action of ultraviolet light. - ·, attacking the head group of PFOS and degrading it. Compared with the G4 group (only sodium persulfate was added) under visible light, the degradation rate and defluorination rate of PFOS in the G5 group (only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 1) under visible light increased by 56% and 28.24%, respectively, indicating that the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial has good visible light catalytic properties.

[0121] The removal rate and defluorination rate of perfluoroheptanoic acid in the water of Example 7 and Comparative Examples 6 to 9 are shown in Table 2.

[0122] Table 2 Removal of perfluoroheptanoic acid in water of each treatment group

[0123]

[0124] As can be seen from Table 2, the method for promoting the removal of perfluorinated compounds in water provided by the present invention also has a relatively obvious removal effect on medium- and long-chain perfluorinated compounds-perfluoroheptanoic acid. Under simulated sunlight, compared with the H2 group (only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 2 was added) and the H3 group (only sodium persulfate was added), the defluorination rate of perfluoroheptanoic acid in the H1 group was increased by 28.6% and 8.8%, respectively. This is because the photocatalysis of Fe3O4 / ZnO / Ag3PO4 and the persulfate catalysis are combined in a heterogeneous catalytic form to form a visible light-persulfate coupling (Vis-persulfate) system dominated by photocatalytic oxidation and with persulfate catalytic oxidation. The dosage of Fe3O4 / ZnO / Ag3PO4 composite nanomaterials in group H1-1 is relatively small. Compared with group H1, the active components used for light response and activation of persulfate are relatively small, and the catalytic oxidation ability of pollutants is relatively weak. Therefore, the removal rate and defluorination rate of perfluoroheptanoic acid are lower than those of group H1. The degradation rate and defluorination rate of PFOS in group H4 (only sodium persulfate was added) under visible light are lower than those in group H3 (only sodium persulfate was added) under simulated sunlight, indicating that the persulfate system can also be activated to produce SO4 under the action of ultraviolet light. - ·, attacking the head group of PFOS and degrading it. Compared with the H4 group (only sodium persulfate was added) under visible light, the degradation rate and defluorination rate of PFOS in the H5 group (only the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial prepared in Example 2) under visible light increased by 30% and 16.69%, respectively, indicating that the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial has good visible light catalytic properties.

[0125] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for removing perfluorinated compounds in water, characterized in that: The following steps are involved: A water body containing perfluorinated compounds is mixed with a Fe3O4 / ZnO / Ag3PO4 composite nanomaterial and persulfate, and the perfluorinated compounds in the reaction system are degraded by photocatalytic oxidation coupled with persulfate catalytic oxidation under sunlight or simulated sunlight conditions; the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial is composed of a composite of Fe3O4 nanocrystal clusters, ZnO nanotubes and Ag3PO4 nanoparticles, the Fe3O4 nanocrystal clusters are encapsulated inside the ZnO nanotubes, and the Ag3PO4 nanoparticles are loaded on the ZnO nanotubes; the mass of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in the reaction system is 0.01-0.05 g / L; the concentration of the persulfate in the reaction system is 0.25-0.3 mmol / L; The pH value is 6.5-7.5; after the reaction is completed, the magnetic properties of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial are used to separate and recover it from the reaction system; the persulfate is selected from peroxymonosulfate or peroxydisulfate; the peroxymonosulfate is selected from any one or more of potassium peroxymonosulfate composite salt or sodium peroxymonosulfate composite salt; the peroxydisulfate is selected from any one or more of sodium peroxydisulfate, potassium peroxydisulfate or ammonium peroxydisulfate; the light source for simulating sunlight is selected from any one or more of a xenon lamp, a halogen lamp or an LED lamp; the degradation time is 6-24h; the perfluoro compound is a long-chain perfluoro compound or a medium-chain perfluoro compound; the long-chain perfluoro compound includes perfluorooctyl carboxylic acid and perfluorooctyl sulfonic acid; the medium-chain perfluoro compound includes perfluorohexanoic acid and perfluoroheptanoic acid.

2. The method for removing perfluorinated compounds in water according to claim 1, characterized in that: The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial comprises the following steps: (1) adding the activated Fe3O4 nanocrystal clusters into a zinc salt solution and dispersing them evenly to obtain a mixed solution; (2) heating the mixed solution in an inert atmosphere, and adding an alkaline solution dropwise under magnetic stirring to react and obtain Fe3O4 / ZnO; (3) Add Fe3O4 / ZnO to AgNO3 solution, mix well, add hydrogen phosphate solution dropwise while stirring, and react fully to obtain Fe3O4 / ZnO / Ag3PO4 composite nanomaterials.

3. The method for removing perfluorinated compounds in water according to claim 2, characterized in that: The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in step (1) includes one or more of the following features: (1a) The Fe3O4 nanocrystal clusters are prepared by a solvothermal method; (1b) The activation treatment is performed by placing the Fe3O4 nanocrystal clusters in an activator solution and performing ultrasonic treatment; (1c) the zinc salt of the zinc salt solution is selected from any one or more of zinc acetate, zinc sulfate, zinc chloride or zinc nitrate; (1d) the molar concentration of the zinc salt solution is 0.001 to 0.01 mol / L; (1e) The dispersion method is ultrasonic treatment for 15 to 60 minutes.

4. The method for removing perfluorinated compounds in water according to claim 3, characterized in that: The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in step (1) includes one or more of the following features: (1b1) The activator is sodium citrate or sodium malate; (1b2) the mass fraction of the activator in the activator solution is 1% to 3%; (1b3) The ultrasonic treatment time is 20 to 40 minutes; (1b4) After the ultrasonic treatment, the mixture needs to be left to stand for 0.5 to 5 hours.

5. The method for removing perfluorinated compounds in water according to claim 2, characterized in that: The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in step (2) includes one or more of the following features: (2a) The inert atmosphere is selected from one or more of nitrogen or argon; (2b) The heating temperature is 25 to 100° C.; (2c) The speed of the magnetic stirring is 120 to 180 r / min -1 ; (2d) the alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution or ammonia solution; (2e) The reaction time is 5 to 12 hours; (2f) After the reaction is completed, the product is washed and dried.

6. The method for removing perfluorinated compounds in water according to claim 5, characterized in that: The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in step (2) includes one or more of the following features: (2d1) The concentration of the sodium hydroxide solution is 0.03 to 0.05 mol / L; (2f1) The washing is performed by alternately rinsing with ethanol and deionized water, and the number of washing times is three times; (2f2) The drying is vacuum drying at a temperature of 50 to 70°C.

7. The method for removing perfluorinated compounds in water according to claim 2, characterized in that: The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in step (3) includes one or more of the following features: (3a) the hydrogen phosphate is selected from Na2HPO4 or K2HPO4; (3b) The amount of AgNO3 and hydrogen phosphate is such that m(Ag3PO4):m(Fe3O4 / ZnO)=10% to 40%; (3c) The reaction time is 0.5 to 6 hours; (3d) after sufficient reaction, it also includes standing; (3e) After the reaction is completed, the product is further dried, washed and dried again.

8. The method for removing perfluorinated compounds in water according to claim 7, characterized in that: The preparation method of the Fe3O4 / ZnO / Ag3PO4 composite nanomaterial in step (3) includes one or more of the following features: (3d1) the standing time is 0.5 to 12 hours; (3e1) The washing is performed by rinsing with deionized water, and the number of washing times is three times; (3e2) The drying temperature of the primary drying is 50 to 80°C; and the drying temperature of the secondary drying is 35 to 50°C.

Citation Information

Patent Citations

  • Preparation method of industrial water fluorine removal agent

    CN104085973A

  • Perfluorinated compound degrading filtering column, preparation method thereof and perfluorinated compound degrading device

    CN105692852A